Carbon dioxide diffusion coefficient in noninvasive high‐frequency oscillatory ventilation. Issue 6 (17th April 2019) - Schäfer, Christoph; Schumann, Stefan; Fuchs, Hans; Klotz, Daniel
Abstract: Objectives: The carbon dioxide (CO2 ) diffusion coefficient (DCO2 ) reflects CO2 removal during high‐frequency oscillatory ventilation (HFOV). We hypothesized that despite leak flow during noninvasive HFOV (nHFOV) DCO2 continues to indicate ventilation efficacy. Methods: A neonatal airway model including CO2 production and an adjustable oropharyngeal leak was connected to a ventilator via bi‐nasal prongs. Pressures and gas flows were measured at prongs, trachea, and leak. Oscillatory tidal volumes below ( V T trachea ) and above the leak ( V T prong ) were calculated from tracheal and leak flows. DCO2 was calculated using V T trachea (DCO2 trachea ) and V T prong (DCO2 prong ) and compared with CO2 partial pressure (pCO2 ). Effects of leak flow (0, 5, or 10 L/min) on DCO2 were assessed at fixed pressure amplitudes or predefined oscillatory volumes under steady‐state pCO2 conditions in the modeled lung. Results: DCO2 trachea correlated strongly with pCO2, independent of the leak flow level ( P  < 0.0001). DCO2 prong correlated with pCO2 without and with moderate leak ( P  < 0.0001) but not with maximum leak ( P  = 0.1432). V T trachea correlated with the quotient of tracheal pressure amplitude and frequency irrespective of the leak ( P  < 0.0001). Based on the pressure amplitude at prong level ( A prong ) V T trachea continued to follow a linear model of which the slopes decreased with increasing leak flow. V T prong correlated with the quotient of A prong and frequency, irrespective of the leak ( P  < 0.0001). Conclusions: DCO2 obtained at the airway opening at prong level reflects ventilation efficacy during nHFOV even in the presence of moderate oropharyngeal leak.